EUROPEAN VALUES AND GEORGIA (IN THE LIGHT OF MERAB MAMARDASHVILI’S VIEW) - Labuchidze, Dodo (Darejan) (European Scientific Journal, ESJ, 2014)
The spectrum of the problems analyzed in the following article is based on the works by Merab Mamardashvili (1930-1990) dedicated to the theme of Europe, talks given in Paris and Barcelona, articles and interviews published in various French newspapers or journals. Mamardashvili clearly realized that the establishment of democratic regime in the society emerging on the ruins of a totalitarian state could create the most complicated problem to the state and culture; that the indigenous peoples of the former Soviet Union (including Georgians) who before October Revolution could not follow the time, modernity, would find themselves in a difficult situation in the process of formation of civil society and its members as citizens. The aspiration toward modernizing the individuals poses many difficulties to the politicians and citizens because we are simultaneously being transformed into free and independent nation, and the members of civil society. The situation is complicated by the fact that this process passes through the fog of post-totalitarian society. Merab Mamardashili’s critical analysis is due to a desire for better future of Georgia, the desire that in the era of globalization Georgian thinking could adequately respond to the challenges of time. In the process of desovietization of thinking and formation of civil society, the views developed by the philosopher Merab Mamardashili about the relationships between the individual and society are still valuable and relevant.